Meeting the communication needs of students on the autism spectrum in Australian classrooms: Adjustments reported by educators and specialists. (4th March 2021) - Harper-Hill, Keely; Trembath, David; Clark, Megan; Bruck, Susan; Saggers, Beth
Abstract: Purpose: The purpose of this study was to examine educators' and specialists' provision of communication adjustments for students on the autism spectrum in mainstream and supported education settings. Method: Secondary analysis of data collected from educators and specialists in the Australian Autism Educational Needs Analysis was undertaken. Thematic analysis of adjustment descriptions identified 11 categories. The use of the 11 specific adjustment categories with reference to (a) participant group (educator versus specialists), and (b) setting (mainstream versus supported) were described and associations investigated using Chi-square analyses. Result: Only 32% of the 381 educators and specialists reported using adjustments. Of the adjustments reported, those categorised as "Multimodal Communication", "Structured Teaching", and "Assistive Technology" were frequently included by both groups. Significant associations were apparent between groups and the use of specific adjustments including naturalistic communication strategies. Significant differences were evident in the proportion of specific adjustments used by participants in supported as opposed to mainstream settings. Conclusion: Possible reasons for the differences in the adjustments reported by educators and specialists and the role that setting may play in these are discussed. These include resourcing, the choice of adjustment being driven by school setting rather than student need, and possible differences between professionals in describing the adjustments made.